Ventricular remodeling induced by retinoic acid supplementation in adult rats - de Paiva, SAR; Zornoff, Leonardo Antonio Mamede [UNESP]; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Cicogna, Antonio Carlos [UNESP]; Campana, A. O. (Amer Physiological Soc, 2003)
Retinoic acid (RA) plays a role in regulating cardiac geometry and function throughout life. The aim of this study was to analyze the cardiac effects of RA in adult rats. Wistar rats were randomly allocated to a control group (n = 18) receiving standard rat chow and a group treated with RA (n = 14) receiving standard rat chow supplemented with RA for 90 days. All animals were evaluated by echocardiography, isolated papillary muscle function, and morphological studies. Whereas the RA-treated group developed an increase in both left ventricular (LV) mass and LV end-diastolic diameter, the ratio of LV wall thickness to LV end-diastolic diameter remained unchanged when compared with the control group. In the isolated papillary muscle preparation, RA treatment decreased the time to peak developed tension and increased the maximum velocity of isometric relengthening, indicating that systolic and diastolic function was improved. Although RA treatment produced an increase in myocyte cross-sectional area, the myocardial collagen volume fraction was similar to controls. Thus our study demonstrates that small physiological doses of RA induce ventricular remodeling resembling compensated volume-overload hypertrophy in rats.
Keywords: hypertrophy; echocardiography; papillary muscle; collagen